Students’ Perception on Extensive Listening at English Study Program PSDKU Maluku Barat Daya - Meikudy, Marsel; Binnendyk, Sophia; Meyer, Fredi (Koli Journal : English Language Education, 2024)
This research addresses a significant gap in language learning research by investigating students' perceptions of extensive listening, a crucial yet understudied component of language learning. Despite its proven effectiveness in improving listening skills, more is needed to know about students' experiences and attitudes toward extensive listening. This study filled this gap by exploring students' perspectives at Pattimura University's campus in Southwest Maluku. By using a quantitative method and Likert scale questionnaires, the research revealed a positive student attitude toward extensive listening classes and activities. These findings have important implications for language learning practices, highlighting the need to consider students' perceptions in designing practical, extensive listening activities. This study contributed to bridging the gap between theory and practice, in enhancing our understanding of extensive listening' role in language learning.